Patronage and clientage between God, Israel and the nations : a social-scientific investigation of Psalm 47 - Schader, Jo-Mari (Journal for Semitics, 2010)
The author of Psalm 47 appears to be occupied with the relationship of three role-players, namely God, Israel and the nations. The relationship of the three role-players is investigated by employing a social-scientific and semantic investigation into terminology used in Psalm 47 referring to patronage and clientage as the form of the relationship between them. A brief overview is also given of how patron-client/vassal relationships functioned in the ancient Near East. The result of this study is that Psalm 47 clearly contains a universal perspective on the relationship between God, Israel and the nations and that God serves as the universal patron over Israel and the nations, with the nations being subject to the patronage of Israel.
paid